E-Waste Management: An Analysis under the Perspective of Conflicts and Shared Responsibility - Layanne Nara Parente Cardoso; Karla Danyelle de Oliveira Miranda; Ednael Francisco Vieira da Silva; Patricia Guarnieri; José Leão e Silva Filho; Lúcio Camara e Silva (Logistics)
Background: The Brazilian National Solid Waste Policy establishes the shared responsibility of all actors involved in e-waste generation and management; however, some conflicts of interest need interventions and approaches for preventing them. Objective: This paper proposes using a graph model for conflict resolution (GMCR) decision support system to simulate the analysis and resolution of realistic e-waste management conflicts. Method: A systematic literature review focused on e-waste management, shared responsibility and conflict management was conducted, and a graph model for conflict resolution (GMCR) decision support system was applied to generate a framework to address this context. Results: The need for commitment agreements promoted by government institutions in partnerships with companies involved in the process is essential since the principle of shared responsibility requires educational actions, favoring efficiency in the reverse logistics recovery procedures for e-waste. Understanding the interconnected causes of conflicts and their facets is crucial for effective resolution and prevention, aiding comprehension, focused interventions, and evidence-based decision-making for transformative change amidst conflicting stakeholder objectives in the case of WEEE management. These results can be helpful for academics and practitioners working in this area.